Insect pests of maize in storage: biology and control - Kossou, D.K.; Bosque Pérez, N.A. (1998)
Damage and losses to stored maize in Africa are often severe. Storage pests of an area have to be identified to determine whether they merit control and to choose appropriate control methods. Know ledge of the biology of pests and of factors influencing preharvest and postharvest infeststion is important to control insect pests in maize storage.